A Novel Major Pilin Subunit Protein FimM Is Involved in Adhesion of Bifidobacterium longum BBMN68 to Intestinal Epithelial Cells - Xiong, Yao; Zhai, Zhengyuan; Lei, Yuanqiu; Xiao, Bingbing; Hao, Yanling (Frontiers in Microbiology, 2020)
Adhesion to gastrointestinal tract is considered important for bifidobacteria to colonize in human gut and thus exert probiotic effects. Some cell surface proteins of bifidobacteria, known as adhesin, play critical roles in binding to host cells or extracellular matrix (ECM). To elucidate the adhesion mechanism of centenarian-originated probiotic Bifidobacterium longum BBMN68, 560 extracellular proteins were predicted using PSORTdb. Twenty-one proteins were further identified as putative adhesion protein by NCBI’s conserved domain database, and then over-expressed in heterologous host Lactococcus lactis NZ9000. It is noteworthy that the recombinant strain expressing FimM showed significantly increased adhesion ability to both HT-29 cell and mucus secreted cell LS174T, i.e. 2.2 and 5.4-fold higher than that of the control strain, respectively. Amino acid sequence alignment showed that FimM was major pilin subunit protein containing a Cna-B type domain and C-terminal LPKTG sequence. However, in silico analysis revealed that BBMN68_RS10200 encoding a pilus-specific class C sortase in fimM-coding cluster was pseudo gene, indicating that FimM could act as surface adhesion monomer without polymerization into pili-like structure. Immunogold electron microscopy results further confirmed that FimM were visualized on the surface of L. lactis NZfimM and B. longum BBMN68 as monomer. Moreover, the adhesion to human receptors fibronectin, fibrinogen and mucin were 3.8, 2.1 and 3.1-fold increased by overexpressing FimM. The binding specificity of FimM was further verified by inhibition assay with anti-FimM antibodies. In addition, homologs of FimM was found in B. bifidum 85B, B. gallinarum CACC 51426 and 26 other B. longum strains by sequence similarity analysis with BLASTP. Therefore, FimM is a novel surface adhesin which is mainly present in B. longum strains.